DINAMIKA RITUAL TAREKAT SAMMÂNIYAH PALEMBANG - Munir, - (Madania: Jurnal Kajian Keislaman, 2016)
Ritual Dynamic of Tarekat Sammâniyah in Palembang. Study of ritual and teaching of tarekat Sammâniyah has been reraly observed by many scholarly people. To find its publication on scientific literatures is still hard;a different publication from other sufism sects such as Qadîriyah, Naqsabandiyah, and Syattâriyah that can befaund easily. Whereas, historically, the Sammâniyah sect had been a formal school of Sufism in various Islamic Nusantara Sultanates such as in Palembang (South Sumatera), Banjar (South Kalimantan), Goa (South Sulawesi),and Siak (Riau). The analysis used in this study is continuity and change approach as well as analysis of critical and phenomenological exegesis. It was concluded that Sammâniyah sect of Sufism in Palembang consisted of processof baiat, suluk, legalization, expression of gratitude to God, brideprice, zikir, and Ratib Sammâniyah